IMBALANCES IN THE FINANCIAL AND ECONOMIC SYSTEM: IDENTIFICATION AND CAUSATION - Фролов, Сергій Михайлович; Орлов, Володимир Володимирович; Диха, Марія Василівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Abstract. The article systematizes the conceptual and categorical apparatus for the interpretation of imbalance. To understand the importance of studying the issue of imbalances, a review of the results of research in the field of finance, published in the international scientometric database Scopus. Using VOSviewer 1.6.15, a map of relationships in research on financial imbalances has been developed. The authors prove that imbalances in the field of finance are manifested at the global level, at the level of public finances and the implementation of monetary and fiscal policies, as well as have an impact on investment. Based on the keywords that defined the formed clusters, imbalances are characteristic of all areas or sectors of the financial system and are due to the lack of stability in financial relations. The imbalances that are manifested in the trade deficit or overproduction of certain types of goods are identified; labor shortages or unemployment due to lack of jobs; capital shortages in general or in individual sectors of the economy; imbalance of export-import operations; imbalances in public finance, stock market imbalances, etc. Imbalances cause the formation of certain macroeconomic trends that lead to structural changes. The article presents the author’s coverage of the relationships and evolution of the economic system and its subsystems through the prism of structural change; a simplified algorithm for determining the state of imbalance, identification and assessment of macroeconomic imbalances is provided. There is a direct connection between the terms "structural change", "structural shift" and "structural transformation". It is in this sequence that they cause the renewal of the financial and economic system. In addition, structural changes-shifts-transformations are directly caused by the action of imbalances, and the latter, in turn, also occur under the influence of structural changes and transformations; that is, there are direct and inverse relationships between imbalances and structural change-shift-transformation processes. Therefore, in order to reach a qualitatively new balanced economic development (ie an updated level of functioning of the financial and economic system), all efforts should be aimed at ensuring "manageable imbalances", constructive action and achieving positive effects from change.